Prevalence of immunological failure and durability of first line antiretroviral therapy at Bugando Hospital Mwanza, Tanzania (Tanzania Medical Journal, 2010)
Background: Highly active antiretroviral therapy (HAART) for the treatment of HIV infection has led to profound reductions in the incidence of mortality due to AIDS-related causes in recent years. Immunological status is common parameter used to monitor HIV treatment success in developing countries. This a crossectional retrospective follow up study was conducted to determine the prevalence of immunological treatment failure and risk factors associated to it among patients on ARV therapy at Bugando MedicalCentre. Method: A crossectional Retrospective study was conducted amongall patients on ART from 2005 attending BMC CTC clinic. Using standard data collection form all demographic data, adherence levels, and CD4 + counts were recorded and analyzed using SPSS 11.5 computer software to determine the prevalence and predictors of immunological failure. Results: A total of 2975 patients were on ART during the study period, in the analysis 362 patients were included and followed backwards for mean duration of 29 months. The base line CD4 of more than 100cells/?l was found in 43.6% of patients studied. A steady CD4 increase in the first 7 months, followed by slow increase in subsequent months was noted. The prevalence of immunological treatment failure was 17.1% (95% CI 17.1%±3.9). Adherence below 95% was strongly associated with immunological treatment failure (p=0.00001). There was significant association between baseline CD4 of more than 100cell/ ?l and immunological treatment failure (p=0.001). No significant difference was found between Home based care (HBCP) and immunological treatment failure (p=0.06). The average time to treatment failure for the first line regimen was 20 months, with 59% of failed patients having a lag time of 5 weeks before appropriate changes in their ART regimen were done. Conclusions and recommendation: Immunological failure was significantly associated with adherence below 95% and low baseline CD4 count of less than 100cells/?l. The multi-disciplinary HIV treatment and care should reinforce adherence during each patient encounter. Strategies to maximise adherence will help to ensure treatment success. We also recommend early HIV testing and referral to care before severe immnosuppression develops. A switch to second line ARV regimen should be considered after a period of adherence intensification.Key words: Immunological failure, CD4, Prevalence, HAART, HIV